2006
DOI: 10.1007/s00441-006-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neurons that express 5-hydroxytryptamine4 receptors in intestine

Abstract: 5-Hydroxytryptamine (5-HT) is an endogenous stimulant of intestinal propulsive reflexes. It exerts its effects partly through 5-HT4 receptors; 5-HT4 receptor agonists that are stimulants of intestinal transit are in clinical use. Both pharmacological and recent immunohistochemical studies indicate that 5-HT4 receptors are present on enteric neurons but the specific neurons that express the receptors have not been determined. In the present work, we describe the characterization of an anti-5-HT4 receptor antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…While 5-HT 3 receptors have been confirmed in the myenteric plexus, the role and location of 5-HT 4 receptors are subjects of debate in the literature (21,22,27,31,38). The presence of 5-HT 4 receptors has been confirmed on submucosal and myenteric ISNs projecting to the mucosa in guinea pig small intestine (33) and may be involved in the regulation of motility (32). Li et al (25) observed decreased motility in tryptophan hydroxylase (TPH) type 2 (TPH2) knockout mice, which lack the neuronal isoform of TPH2, the rate-limiting enzyme in 5-HT biosynthesis; however, TPH1 knockout mice lacking the nonneuronal isoform expressed in EC cells did not show altered motility.…”
mentioning
confidence: 95%
“…While 5-HT 3 receptors have been confirmed in the myenteric plexus, the role and location of 5-HT 4 receptors are subjects of debate in the literature (21,22,27,31,38). The presence of 5-HT 4 receptors has been confirmed on submucosal and myenteric ISNs projecting to the mucosa in guinea pig small intestine (33) and may be involved in the regulation of motility (32). Li et al (25) observed decreased motility in tryptophan hydroxylase (TPH) type 2 (TPH2) knockout mice, which lack the neuronal isoform of TPH2, the rate-limiting enzyme in 5-HT biosynthesis; however, TPH1 knockout mice lacking the nonneuronal isoform expressed in EC cells did not show altered motility.…”
mentioning
confidence: 95%
“…They exhibit slow EPSPs in response to trains of stimuli [10] and express immunoreactivity for NK 1 [73], 5-HT 4 [100], GluR1 [69] and CRF1 receptors [71] (Table 1). Some excitatory input comes from myenteric AH/Dogiel type II neurons [42], which express tachykinins [16], suggesting that the slow EPSPs are mediated via NK 1 receptors.…”
Section: Secretomotor Pathwaysmentioning
confidence: 99%
“…11 Of the 7 classes of 5-HT receptors, 5-HT 1 , 5-HT 2 , 5-HT 3 , 5-HT 4 , and 5-HT 7 receptors are known to be expressed in the gastrointestinal tract and to affect gastrointestinal motor function. [12][13][14][15][16][17][18][19][20] The role of 5-HT in regulating gastrointestinal motility by mediating the transduction of luminal signals across the mucosa and by participating in enteric neurotransmission is well established. 21,22 There is however significant evidence, mostly from outside the gastrointestinal tract but also in studies on enteric nervous system development, that shows that 5-HT can also regulate cell survival and proliferation.…”
mentioning
confidence: 99%